Enhanced Adaptability to Limited Water Supply Regulated by Diethyl Aminoethyl Hexanoate (DA-6) Associated With Lipidomic Reprogramming in Two White Clover Genotypes - Hassan, Muhammad Jawad; Qi, Hongyin; Cheng, Bizhen; Hussain, Shafiq; Peng, Yan; Liu, Wei; Feng, Guangyan; Zhao, Junming; Li, Zhou (Frontiers in Plant Science, 2022)
Membrane lipid reprogramming is one of the most important adaptive strategies in plant species under unfavorable environmental circumstances. Therefore, the present experiment was conducted to elucidate the effect of diethyl aminoethyl hexanoate (DA-6), a novel synthetic plant growth regulator, on oxidative damage, photosynthetic performance, changes in lipidomic profile, and unsaturation index of lipids in two white clover (Trifolium repens) cultivars (drought-sensitive “Ladino” and drought-resistant “Riverdel”) under PEG-6000-induced water-deficit stress. Results revealed that water-deficit stress significantly enhanced oxidative damage and decreased photosynthetic functions in both cultivars. However, the damage was less in Riverdel. In addition, water-deficit stress significantly decreased the relative content of monogalactocyl-diacylglycerols (MGDG), sulfoquinovosyl-diacylglycerols (SQDG), phosphatidic acisd (PA), phosphatidyl-ethanolamines (PE), phosphatidyl-glycerols (PG), phosphatidyl-serines (PS), ceramides (Cer), hexosylmonoceramides (Hex1Cer), sphingomyelins (SM), and sphingosines (Sph) in both cultivars, but a more pronounced decline was observed in Ladino. Exogenous application of DA-6 significantly increased the relative content of digalactocyl-diacylglycerols (DGDG), monogalactocyl-diacylglycerolsabstra (MGDG), sulfoquinovosyl-diacylglycerols (SQDG), phosphatidic acids (PA), phosphatidyl-ethanolamines (PE), phosphatidyl-glycerols (PG), phosphatidyl-inositols (PI), phosphatidyl-serines (PS), ceramides (Cer), hexosylmonoceramides (Hex1Cer), neutral glycosphingolipids (CerG2GNAc1), and sphingosines (Sph) in the two cultivars under water-deficit stress. DA-6-treated Riverdel exhibited a significantly higher DGDG:MGDG ratio and relative content of sphingomyelins (SM) than untreated plants in response to water deficiency. Furthermore, the DA-6-pretreated plants increased the unsaturation index of phosphatidic acids (PA) and phosphatidylinositols (PI) in Ladino, ceramides (Cer) and hexosylmonoceramides (Hex1Cer) in Riverdel, and sulfoquinovosyl-diacylglycerols (SQDG) in both cultivars under water stress. These results suggested that DA-6 regulated drought resistance in white clover could be associated with increased lipid content and reprogramming, higher DGDG:MGDG ratio, and improved unsaturation index of lipids, contributing to enhanced membrane stability, integrity, fluidity, and downstream signaling transduction.